Новые виды мермитид (Nematode, Mermithidae) Украины - Рубцов, И.А.; Андреева, Р.В. (Вестник зоологии, 1974)
Three new species of Mermithidae are described by the materials from Kiev and Chernigov regions. Paramermis tabanivora sp. n. is reared of Hybomitra sp. gadfly larval which was found in the water body in the environs of town of Shchors. In the same place postparasitic larva Hexamermis albicans (Sieb.) was found. Gastromermis macrosoma sp. n. is reared of the larva Tabanus automnalis L. collected in the soil near water of Lake Khrestie. Mermithidae Paramermis tenuiloba sp. n. the host of which is unknown was found in the same place.